2019
DOI: 10.21061/jcte.v34i1.a2
|View full text |Cite
|
Sign up to set email alerts
|

Linking Occupational Concentration to Hourly Wages for Non-College Going Individuals

Abstract: One of the stated goals of career and technical education (CTE) is to improve the labor market outcomes of participants. One population of students for which concentration CTE may be particularly beneficial is those who determine they will not pursue postsecondary education. By exploring how occupational concentration-defined as earning three or more credits in a specific CTE cluster-relates to labor market outcomes for non-college participants, this study adds to a growing body of research on the benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Given these realities, this study asks how the increased share of each of these benefits through greater shares of STEMM CTE courses (as a proportion of total STEMM coursetaking) links to students’ college employment. Ongoing work suggests that high levels of investment in a specific CTE field, including STEMM CTE, are associated with higher probabilities of post–high school employment in those fields, though this has not been examined for those in college (Plasman, 2019).…”
Section: High School Stemm Cte Courseworkmentioning
confidence: 99%
“…Given these realities, this study asks how the increased share of each of these benefits through greater shares of STEMM CTE courses (as a proportion of total STEMM coursetaking) links to students’ college employment. Ongoing work suggests that high levels of investment in a specific CTE field, including STEMM CTE, are associated with higher probabilities of post–high school employment in those fields, though this has not been examined for those in college (Plasman, 2019).…”
Section: High School Stemm Cte Courseworkmentioning
confidence: 99%
“…Previous examinations of the link between course‐taking and occupational outcomes (e.g., Plasman, 2019) have been framed in terms of human capital theory (Becker, 1964). This model primarily features knowledge and skills as the main human attributes affected by schooling and posits that they are the major determinants of posteducational outcomes.…”
Section: Social Cognitive Theoriesmentioning
confidence: 99%
“…More recently, Dougherty (2016) found that CTE concentration (defined as students taking three or more courses in CTE programs) was associated with increases in both probability of employment after graduation and wages. Plasman (2019) similarly found that, among noncollege‐going individuals, CTE concentration in health science, trades (comprising concentrations in manufacturing, architecture and construction, or transportation and logistics), and agriculture and natural resources was beneficial in terms of earnings 3 years after graduating from high school.…”
mentioning
confidence: 99%
See 2 more Smart Citations